AAMS 2017
DOI: 10.21276/aams.1756
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of morphometric placental microvessels parameters with birth weight.

Abstract: Introduction: Birth weight (BWT) is greatly affected by placental insufficiency and the microvessels configurations. Aims of this study were to evaluate various parameters: villous density (VD), microvessel density (MVD), microvessels per villus (MVPV), mean microvessel caliber (VC), total microvessels boundary density (TVBD), maximum possible total length of microvessels (MP-TVL) and maximum possible total surface area of microvessels (MP-TVSA) in terminal villi of placenta. All the parameters including place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Several morphometric studies have demonstrated significant and positive correlation between weight of the placenta with weight of newborns and length of gestation (7,(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Several morphometric studies have demonstrated significant and positive correlation between weight of the placenta with weight of newborns and length of gestation (7,(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%